The Influence of Motivation, Organizational Communication, and Compensation on Employee Retention at Cafe Paddy Breeze Warujayeng, Nganjuk - Farikha Andini Putri; Hery Purnomo (Journal of International Conference Proceedings, 2025)
This study aims to examine the influence of motivation, organizational communication, and compensation on employee retention at Cafe Paddy Breeze in Warujayeng, Nganjuk. The research uses a quantitative associative approach involving all café employees to provide an objective understanding of the factors that encourage employees to stay. The findings show that motivation and compensation have a significant positive effect on employee retention, while organizational communication does not show a significant individual impact. Nevertheless, the three variables together contribute significantly to retention. The study adds value to human resource management literature, particularly within the food and beverage sector, by analyzing these variables simultaneously. Practically, the results offer guidance for managers in improving motivation, strengthening communication, and ensuring competitive compensation to reduce turnover. This study is limited by its small sample size and single research site, indicating the need for broader future studies to enhance generalizability.